PELATIHAN DESAIN LOGO DENGAN APLIKASI CANVA DALAM MENINGKATKAN BRANDING UMKM DESA RIDOMANAH - Humairoh, Rizka; Tama, Annafi Indra; Rahmawati, Rafika (An-Nizam, 2024)
Logo design training is one effort that can be made to improve branding for micro, small and medium enterprises (MSMEs). In this case, MSMEs in Ridomanah Village need to strengthen their visual identity to face increasingly fierce market competition. Through this community service program, training is provided in creating logos using the Canva application, which is easy to access and use by MSMEs. The methods used in this training include socialization about the importance of branding, as well as direct practice in designing logos that suit the characteristics of each business. This training is expected to be able to help MSMEs create an attractive and professional visual identity, so as to increase competitiveness, expand market reach and strengthen consumer loyalty. The results of this program are not only beneficial for MSMEs in improving branding, but also provide new insight for business actors regarding the importance of logo design in building a strong business image.